Beyond expropriation without compensation law, land reform and redistributive justice in South Africa - Boggenpoel, Z. T.; Walker, Cherryl; Zenker, Olaf (Cambridge, United Kingdom ; New York, NY Cambridge University Press, 2024)
peeding up land reform through a constitutional amendment that would explicitly permit the expropriation of land without compensation has dominated legal and political-policy debates in South Africa in recent years. Taking this politically and emotionally charged issue as its starting point, this volume offers both expert commentary on this issue from a variety of disciplinary perspectives and also fresh ideas on how to advance the redistributive transformation that South Africa so urgently needs. It brings critically important debates around transformative property law, the need for diversified land justice and the possibilities of alternative forms of redistribution into productive conversation with each other. While grounded in the complex realities of South Africa's past and present, the volume speaks to concerns that resonate in many contexts in the Global South and beyond. It will appeal to scholars, students, policymakers and general readers concerned with both the theory and practice of redistributive justice. This title is also available as Open Access on Cambridge Core.
Politics or Principle? making sense of the expropriation without compensation debate / Zsa-Zsa Boggenpoel -- The legal and philosophical dichotomy between land and property : the rights and wrongs of South African property law : a transformative justice approach / Bulelwa Mabasa, Thomas Ernst Karberg, and Siphosethu Zazela -- The 'justice' in 'just and equitable' compensation / Elmien (WJ) du Plessis -- The tale of two women : transformative thrust embodied in the property clause-in theory only or a lived reality where land reform is concerned? / Juanita M Pienaar -- Setting our transformation sights too low : land reform, 'expropriation without compensation' and 'state custodianship of land' / Danie Brand -- The Constitution's mandate for transformation : from 'expropriation without compensation' to 'equitable access to land' / Ruth Hall -- Land reform opportunities meet democratic challenges in traditional areas : gendered lessons from vernacular law and IPILRA / Sindiso Mnisi Weeks -- Land reform and rural production in South Africa / William Beinart -- Land reform and beyond in times of social-ecological change : perspectives from the Karoo / Cherryl Walker -- Ecological justice, climate shocks, and the challenge of re-agrarianizing South Africa through the food sovereignty commons / Vishwas Satgar -- Redistributive justice, transformational taxes, and the legacies of Apartheid / Heinz Klug -- Redistribution of what? beyond land in the moral politics of distribution / James Ferguson.
itle from publisher's bibliographic system (viewed on 28 Mar 2024).
Keywords: Compensation (Law) -- South Africa; Eminent domain -- South Africa; Transitional justice -- South Africa; Land reform -- Law and legislation -- South Africa; Land tenure -- Law and legislation -- South Africa